Assessment of urban flood vulnerability using the social-ecological-technological systems framework in six US cities. (May 2021) - Chang, Heejun; Pallathadka, Arun; Sauer, Jason; Grimm, Nancy B.; Zimmerman, Rae; Cheng, Chingwen; Iwaniec, David M.; Kim, Yeowon; Lloyd, Robert; McPhearson, Timon; Rosenzweig, Bernice; Troxler, Tiffany; et al.
Highlights: We developed a SETS framework for assessing urban flood vulnerability. We adapted 18 vulnerability indicators representing S, E, and T dimensions. S, E, T flood vulnerable hotspots cluster in specific neighborhoods. The S, E, T indicator combinations better explain S- E-T vulnerability effectively. The overlapping areas of S, E, or T vulnerability can be targeted for improvement. Abstract: As urban populations continue to grow through the 21st century, more people are projected to be at risk of exposure to climate change-induced extreme events. To investigate the complexity of urban floods, this study applied an interlinked social-ecological-technological systems (SETS) vulnerability framework by developing an urban flood vulnerability index for six US cities. Indicators were selected to reflect and illustrate exposure, sensitivity, and adaptive capacity to flooding for each of the three domains of SETS. We quantified 18 indicators and normalized them by the cities' 500-yr floodplain area at the census block group level. Clusters of flood vulnerable areas were identified differently by each SETS domain, and some areas were vulnerable to floods in more than one domain. Results are provided to support decision-making for reducing risks to flooding, by considering social, ecological, and technological vulnerability as well as hotspots where multiple sources of vulnerability coexist. The spatially explicit urban SETS flood vulnerability framework can be transferred to other regions facing challenging urban floods and other types of environmental hazards. Mapping SETS flood vulnerability helps to reveal intersections of complex SETS interactions and inform policy-making for building more resilient cities in the face of extreme events and climate change impacts.